Sheet laying method of bioprosthetic valve material
Through glutaraldehyde cross-linking and polypeptide chain treatment, a stable covalent bond network is formed, which solves the calcification and degradation problems of biological valve materials, improves their stability and durability, and extends their service life.
Patent Information
- Application Number
- CN202510986334.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-17
- Publication Date
- 2025-10-10
- Estimated Expiration
- 2045-07-17
AI Technical Summary
Existing biological valve materials are prone to calcification and degradation, and lack stability and durability. Young patients may need a second surgery to replace them, and they are easily damaged by heart beats and blood flow impact.
Glutaraldehyde solution was used to cross-link the cloth and bovine pericardium sheet, and then treated with polylysine, magnesium chloride and phosphatidylserine solution to form a stable covalent bond and cross-linking network, blocking the calcification and protease hydrolysis pathways and strengthening the collagen fiber structure.
It improves the stability and durability of biological valve materials, extends their service life, reduces the risk of calcification and protease hydrolysis, and enhances the strength and damage resistance of the materials.
Smart Images

Figure BDA0005504521810000081 
Figure BDA0005504521810000091 
Figure HDA0005504521820000011
Abstract
Description
TECHNICAL FIELD
[0001] The application relates to the field of biological valve material processing, in particular to a biological valve material sheeting method. BACKGROUND
[0002] An artificial heart valve is a kind of heart interventional medical device for treating heart valve diseases or defects, The biological valve material is made of animal tissue (for example, pig valve, bovine pericardium), which is compatible with human tissue, and is not prone to cause thrombosis or immune rejection after implantation, and does not need to take anticoagulant drugs for a lifetime after surgery, thereby significantly reducing the risk of bleeding, and is especially suitable for anticoagulation emergency or elderly patients.
[0003] However, the biological valve material is prone to problems such as calcification and degradation, and the average service life is about 10-15 years, and young patients may need to replace the biological valve material by a second surgery, and the biological valve material is long-term impacted by the heart beat and blood flow impact pressure in the human body, and is prone to damage, thereby affecting the stability of the biological valve material.
[0004] Therefore, how to prepare a biological valve material with good durability, high stability, good anti-calcification effect and anti-proteinase hydrolysis is a problem to be solved. SUMMARY
[0005] In order to prepare a biological valve material with good durability, high stability, good anti-calcification effect and anti-proteinase hydrolysis, the application provides a biological valve material sheeting method.
[0006] The biological valve material sheeting method provided by the application adopts the following technical scheme: A biological valve material sheeting method comprises the following steps: S1, after fresh bovine pericardium is cleaned, defatted and subjected to cell removal treatment, bovine pericardium sheets are obtained and prepared for use; S2, a fixed cloth soaked with a glutaraldehyde solution with an infiltration concentration of 0.28-0.32% is prepared and prepared for use; S3, the bovine pericardium sheets are placed on the fixed cloth with the rough surface facing upward and the smooth surface facing downward, and after exhaust, the second bovine pericardium sheet is repeatedly operated according to the above method, so that the bovine pericardium sheets and the fixed cloth are alternately sheeted, and after exhaust, dry cloth is placed on the surface of the uppermost fixed cloth to obtain fixed bovine pericardium sheets; S4, the fixed bovine pericardium sheets are subjected to preliminary treatment with a glutaraldehyde solution with a concentration of 0.28-0.32%, and the storage temperature is 2-8 DEG C; then the bovine pericardium sheets and the fixed cloth after the preliminary treatment are packed, the bovine pericardium sheets are soaked in a glutaraldehyde solution with a concentration of 0.58-0.62% for secondary treatment, and the storage temperature is 2-8 DEG C, to obtain semi-finished products; S5. The semi-finished product is post-processed, preserved, and finally stored at 2-8°C to obtain the finished product.
[0007] By adopting the above technical solution, the fixing cloth is impregnated with glutaraldehyde. The glutaraldehyde molecule contains two active aldehyde groups and can undergo specific condensation with the free amino groups of bovine pericardium collagen in a neutral or weakly alkaline environment to form a stable covalent bond. The glutaraldehyde molecule can also establish an intermolecular cross-linking network between adjacent collagen fibers, thereby improving the spatial stability of the fiber structure and transforming the bovine pericardium from a flexible biological tissue into an engineering material with a certain mechanical strength. The impregnated fixing cloth is laid flatly in contact with the bovine pericardium sheet, and the cross-linking and fixing effect of the glutaraldehyde is combined with the restraint of the fixing cloth to make the cross-linked and fixed bovine pericardium sheet relatively flat and have a certain strength.
[0008] The cross-linking and fixation of bovine pericardium sheets by glutaraldehyde seals the enzymatic degradation sites of collagen, blocks the erosion path of proteases, and prolongs the service life of biological valve materials. Combined with the cross-linking effect of the three-dimensional network structure, it increases the cross-linking density of biological valve materials, further improving the stability of biological valve materials. At the same time, it has the advantages of good resistance to calcification and resistance to protease hydrolysis, thereby extending the service life of biological valve materials.
[0009] Preferably, in S2, the glutaraldehyde solution is poured into the Lock&Lock box to submerge the fixing cloth.
[0010] By adopting the above technical solution, the fixing cloth is ensured to be completely soaked in the glutaraldehyde solution, and bubbles are not easily generated. At the same time, the cross-linking and fixing effect of the glutaraldehyde solution on the bovine pericardium piece is guaranteed, and the cross-linking and fixing density is guaranteed, so that the biological valve material has higher strength and better stability.
[0011] Preferably, in S3, the fixing cloth is gently squeezed to remove 60-70% of the liquid, fixed to the center of the bottom of the Lock & Lock box, and then bubbles are squeezed out, the surface liquid of the bovine pericardium slice is wiped off, and after being stretched flat, the bovine pericardium slice is laid flat on the fixing cloth with the rough surface facing up and the smooth surface facing down. After exhausting, the second bovine pericardium slice is repeated according to the above method, so that the bovine pericardium slices and the fixing cloth are laid alternately. After exhausting, a dry cloth is laid on the surface of the top layer of the fixing cloth to obtain a fixed bovine pericardium slice.
[0012] By adopting the above technical solution, removing excess liquid can ensure the fixed cross-linking stability and structural density of the bovine pericardium sheet, and by exhausting the air, the structural density can be further ensured, so that the biological valve material has better stability and durability.
[0013] Preferably, the dry cloth has 2-4 layers and is polyester fiber cloth.
[0014] By adopting the above technical solution, the overlapping bovine pericardium sheet and the fixed sheet are blocked, and the glutaraldehyde solution is stabilized. This not only prevents the formation of wrinkles and ensures the directional arrangement of collagen fibers, but also protects the bovine pericardium sheet from being easily damaged by external forces. At the same time, it can eliminate bubbles and reduce structural defects formed after cross-linking and fixation, further ensure the stability of the cross-linked fixed structure, and block bacteria from the external environment, further extending the service life and durability of the biological valve material.
[0015] Preferably, the total height of the bovine pericardium sheet, the fixing cloth and the dry cloth after laying is completed is less than 2 / 3 of the Lock & Lock box.
[0016] By adopting the above technical solution, 1 / 3 of the space is reserved to ensure that the glutaraldehyde solution completely submerges the paving structure, thereby preventing uneven cross-linking due to insufficient liquid level inside the pericardium sheet.
[0017] Preferably, the specific steps of post-processing in S5 are as follows: The semi-finished product is first placed in a polylysine composite solution for fixation treatment, then subjected to a secondary fixation treatment in a magnesium chloride composite solution, washed, and then immersed in a glutaraldehyde solution.
[0018] By adopting the above technical solution, after the semi-finished product is treated with glutaraldehyde solution, residual aldehyde groups and other substances remain. The residual unreacted glutaraldehyde monomers and free aldehyde groups become the core sites of calcification. The amino groups of polylysine in the polylysine composite solution are actively combined with the residual aldehyde groups to form stable covalent bonds, reducing the nucleation sites of calcification. In addition, the dense cationic layer formed by polylysine blocks the diffusion path of calcium ions, further preventing calcification. The carboxyl groups of polylysine can enhance the hydrophilicity of the material surface and can also bind to calcium ions to form stable complexes, reducing the free concentration of calcium ions in tissues, reducing calcium salt deposition, and improving the anti-calcification effect of the biological valve material. Finally, the magnesium chloride composite solution is used for treatment. After the polylysine blocks the aldehyde groups, the magnesium chloride further forms a barrier, constructing a double anti-calcification defense line and improving the anti-calcification effect.
[0019] The polylysine composite liquid and the magnesium chloride composite liquid are combined to utilize the linear polypeptide chain of polylysine to penetrate into the gaps between bovine pericardial collagen fibers, further combining with the internal collagen carboxyl groups, reducing the porosity and increasing the structural density. The amino groups in polylysine form covalent bonds with the residual aldehyde groups of glutaraldehyde, adding new molecular bridge points on the basis of the original cross-linked network, further increasing the cross-linking density. The magnesium ions in magnesium chloride combine with the carboxyl groups to further fill the pores and increase the density of the cross-linked structure, thereby improving the strength and stability of the biological valve material and extending the service life and durability of the biological valve material.
[0020] Preferably, the polylysine composite solution is composed of a polylysine solution and a phosphatidylserine solution in a mass ratio of 1:0.1-0.2. During the secondary cross-linking treatment, the polylysine solution is added first and then the phosphatidylserine solution is added.
[0021] By adopting the above technical solution, a polylysine solution and a phosphatidylserine solution are combined, and the residual aldehyde groups after polylysine is cross-linked with glutaraldehyde are used to block the calcium ion binding anchor point. The polypeptide chain of polylysine is further cross-linked with phosphatidylserine to form a cross-linked network layer. The hydrophilic end of phosphatidylserine is cross-linked with polylysine, and the hydrophobic end is isolated from contact with collagen, thereby inhibiting the formation of hydroxyapatite crystal nuclei and improving the anti-calcification effect and anti-protease hydrolysis effect. The formation of the cross-linked network further improves the structural stability. In addition, polylysine and phosphatidylserine can bridge the carboxyl groups of adjacent collagen fibers, reduce the slippage between fibers, further improve the strength and fracture stress of the biological valve material, and thus improve the strength and stability of the biological valve material.
[0022] Preferably, the magnesium chloride composite solution is composed of a magnesium chloride solution and a polyvinyl alcohol-1799 solution in a mass ratio of 1:0.4-0.6.
[0023] By adopting the above technical solution, magnesium ions compete with calcium ions for binding to residual carboxyl groups and glutaraldehyde groups, blocking the calcification starting site, and combined with the hydrophilicity of the dense hydroxyl groups in the polyethylene glycol-1799 molecular chain, further hindering the nucleation of calcium crystals; after the magnesium ions are adsorbed on the collagen surface, polyvinyl alcohol-1799 connects with polylysine and phosphatidylserine to form a barrier, preventing calcium deposition and improving the anti-protease hydrolysis effect; and the magnesium ions bind adjacent collagen fibers, reducing fiber slippage, improving the strength and elasticity of the biological valve material, and combined with the barrier network formed by polyvinyl alcohol-1799, further improving the strength and durability of the biological valve material.
[0024] Preferably, the fixing cloth is made of polyester fiber cloth.
[0025] By adopting the above technical solution, when the moist bovine pericardium sheet is spread on the surface of the polyester fiber cloth, the tensile strength of the polyester fiber cloth can absorb the local shear force generated by the spreading operation, reduce the risk of collagen microfiber breakage, and further ensure the stability of the biological valve material.
[0026] Preferably, the polyester fiber cloth is treated as follows: the pretreated polyester fiber cloth is immersed in physiological saline, taken out and dried, then placed in a polyethylene glycol-silver powder composite solution for immersion and dispersion treatment, and then the pretreated polyester fiber cloth is taken out and dried to obtain the polyester fiber cloth.
[0027] By adopting the above technical solution, the connecting effect of polyethylene glycol and glutaraldehyde is utilized to ensure that glutaraldehyde evenly penetrates between each layer. Combined with the antibacterial effect of silver powder, the biological valve material is not easily affected by bacteria. In addition, the binding of polyethylene glycol on the surface of the pretreated polyester fiber cloth allows the silver powder to be stably attached to the surface of the polyester fiber cloth, while also facilitating the discharge of bubbles, thereby completing the paving of the biological valve material.
[0028] In summary, this application has the following beneficial effects: 1. The bovine pericardium piece used as the bioprosthetic valve material has a smooth appearance, uniform thickness, and no bubbles; 2. The bovine pericardium sheet, a bioprosthetic valve material, has stable mechanical properties and is not easily deformed; 3. The bovine pericardium sheet, a biological valve material, has good thermodynamic properties, and its thermal shrinkage temperature reaches above 85°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a schematic diagram of the stretched and fixed cloth in this application; Figure 2 This is a schematic diagram of the fixed cloth laid in this application; Figure 3 This is a schematic diagram of laying bovine pericardium slices in this application; Figure 4 This is a schematic diagram of the bovine pericardium tablets in the Lock & Lock box after repackaging in this application. DETAILED DESCRIPTION
[0030] The present application is further described in detail below with reference to the embodiments.
[0031] Preparation example of polylysine composite solution Among the following raw materials, polylysine was purchased from Shandong Xinxiong Biotechnology Co., Ltd. as food-grade ε-polylysine; phosphatidylserine was purchased from Hebei Qiansheng Biotechnology Co., Ltd.; and other raw materials were all commercially available.
[0032] Preparation Example 1: Polylysine composite solution was prepared by the following method: Weigh polylysine, place it in water and stir until it is completely dissolved to obtain a 1% polylysine solution; Phosphatidylserine is placed in isopropanol and stirred until completely dissolved to obtain a phosphatidylserine solution with a mass fraction of 1%; the isopropanol concentration is 95%.
[0033] Preparation example of magnesium chloride composite solution The following raw materials are all commercially available.
[0034] Preparation Example 2: Magnesium chloride composite solution was prepared by the following method: Magnesium chloride is placed in water and stirred until completely dissolved to obtain a 1% by mass magnesium chloride solution. Polyvinyl alcohol-1799 is placed in 95°C hot water and stirred until completely dissolved to obtain a 1% by mass polyvinyl alcohol-1799 solution. 1 kg of the magnesium chloride solution and 0.5 kg of the polyvinyl alcohol-1799 solution are mixed and stirred to obtain a magnesium chloride composite solution.
[0035] Preparation Example 3: This preparation example differs from Preparation Example 2 in that: 1 kg of magnesium chloride solution and 0.4 kg of polyvinyl alcohol-1799 solution were mixed and stirred to obtain a magnesium chloride composite solution.
[0036] Preparation Example 4: This preparation example differs from Preparation Example 2 in that: 1 kg of magnesium chloride solution and 0.6 kg of polyvinyl alcohol-1799 solution were mixed and stirred to obtain a magnesium chloride composite solution.
[0037] Preparation example of polyester fiber cloth Among the following raw materials, the pretreated polyester fiber cloth was purchased from Hejian Qingfeng Asbestos Chemical Co., Ltd., with a gauge of 18; the other raw materials were all commercially available.
[0038] Preparation Example 5: Polyester fiber cloth was prepared by the following method: The polyethylene glycol is placed in water and stirred until it is completely dissolved. The polyethylene glycol is polyethylene glycol 2000 to obtain a polyethylene glycol solution with a mass fraction of 2%. 0.2 kg of silver powder is dispersed in 1 kg of the polyethylene glycol solution. The silver powder is a nano-silver powder with a particle size of 100 nm. The dispersion is performed by ultrasonic dispersion at a frequency of 20 kHz for 5 minutes. The mixture is mixed to obtain a polyethylene glycol-silver powder composite solution. The pretreated polyester fiber cloth was soaked in physiological saline for 10 minutes, taken out, dried, and then soaked in a polyvinyl alcohol-silver powder composite solution for 10 minutes. During the soaking process, ultrasound was performed at 20 kHz for 5 minutes, and then the pretreated polyester fiber cloth was taken out and dried to obtain a polyester fiber cloth. Example
[0039] The following raw materials are all commercially available.
[0040] Example 1: A method for laying out a bioprosthetic valve material: S1. Wash fresh bovine pericardium with clean water, remove excess surface fat tissue, cut off a relatively uniform part of the precordial area, and store in ice-cold physiological saline. Then, add 0.01M Tris-HCl (pH 8.0) buffer containing 0.2g EDTA and 100μg PMSF in a ratio of 1:4 (weight: volume), shake at 4°C for 4 hours at a frequency of 120rpm, pour out the liquid to retain the bovine pericardium, and wash it three times with physiological saline; then, add 0.05M Tris-HCl (pH 8.0) buffer containing 0.5% Triton X-100, 1% deoxycholic acid, 0.2g EDTA, and 100μg PMSF in a ratio of 1:4 (weight: volume), shake at 4°C for 4 hours at a frequency of 120rpm, pour out the liquid to retain the bovine pericardium, and wash it three times with physiological saline to complete the decellularization process and obtain bovine pericardium slices for use. Storage is refrigerated in a medical refrigerator; S2. Take a Lock & Lock box, place a fixing cloth in the Lock & Lock box, pour 0.3% glutaraldehyde solution into the Lock & Lock box, immerse the fixing cloth, and make sure that the fixing cloth is fully soaked with the 0.3% glutaraldehyde solution, and set aside; the fixing cloth is a polyester fiber cloth; S3. Take a Lock & Lock box as a container for cross-linking and fixing the bovine pericardium slices. Two production personnel, one each, take a piece of fixing cloth soaked in 0.3% glutaraldehyde solution. Gently squeeze the fixing cloth to remove 60% of the liquid, keeping the fixing cloth moist. The two personnel each stretch the fixing cloth from one side to the other, and work together to stretch the fixing cloth flat in the center of the bottom of the Lock & Lock box. If bubbles are generated, they should be expelled. The surface of the fixing cloth should be flat, without wrinkles, overlaps, or creases. Lay three layers of fixing cloth (see Figure 1 and Figure 2 ); After removing the liquid from the surface of the beef pericardium slice in S1, two people each stretch the two corners of the beef pericardium slice and work together to slowly flatten the beef pericardium slice. With the rough side of the beef pericardium slice facing up and the smooth side facing down, lay the beef pericardium slice flat on the fixing cloth so that the beef pericardium slice fits completely in the center of the fixing cloth (see Figure 3 ), during this process, tension should not be used to pull the bovine pericardium sheet. If bubbles are generated, they should be expelled. The surface of the bovine pericardium sheet should not have any artificial wrinkles, overlaps, or bubbles. The first bovine pericardium sheet is paved; the second bovine pericardium sheet is paved according to the above method, and the bovine pericardium sheet and the fixing cloth are alternately paved. After all the bovine pericardium sheets are paved, the top layer is paved with dry cloth according to the above method. The dry cloth is polyester fiber cloth. Three layers of dry cloth are paved. During the paving process, the bovine pericardium sheet and the fixing cloth should not have any wrinkles, folds, or bubbles that affect the flatness of the bovine pericardium sheet. The total height after the bovine pericardium sheet and the fixing cloth are alternately paved should be less than two-thirds of the height of the Lock & Lock box. This is a fixed bovine pericardium sheet. When this height is reached, another Lock & Lock box is used for paving again. S4. One person gently presses the material in the Lock & Lock box with the palm of his hand, and another person pours 0.3% glutaraldehyde solution into the Lock & Lock box with the bovine pericardium piece fixed using a 1000mL measuring cylinder filled with 0.3% glutaraldehyde solution, and slowly pours it along the inner wall of the Lock & Lock box to allow the 0.3% glutaraldehyde solution to fully penetrate the bovine pericardium piece and the fixing cloth. The volume of the 0.3% glutaraldehyde solution poured should be level with the height of the top layer of fixing cloth in the Lock & Lock box. During the process, avoid floating or shifting of the bovine pericardium piece and the fixing cloth. Cover and label the box, place it in a medical refrigerator, and store it at a storage temperature of 4°C for 48 hours to complete the preliminary treatment; take the Lock & Lock box that has completed the preliminary treatment with 0.3% glutaraldehyde solution out of the medical refrigerator in the general production area, wipe the surface of the Lock & Lock box with a dust-free cloth, and pass it to the 10,000-level production area through the transfer window. After cleaning the surface with 75% alcohol, open the Lock & Lock box and transfer the fixing cloth and bovine pericardium slices from the Lock & Lock box one by one from top to bottom. The transferred bovine pericardium slices and fixing cloth are divided into two Lock & Lock boxes. The bovine pericardium slices should be laid flat and stacked in the center of the Lock & Lock box in order. The original shape should be maintained during the transfer process. No folding, tearing or other operations that damage the shape of the bovine pericardium should be performed. After the fixing cloth is collected, it should be cleaned, dried and stored according to the regulations. One person presses the top of the bovine pericardium slice in the Lock & Lock box with the palm of his hand. One person uses a 1000mL graduated cylinder filled with 0.6% glutaraldehyde solution to pour 0.6% glutaraldehyde solution into the Lock & Lock box containing the transferred bovine pericardium slices. The solution should be poured slowly along the inner wall of the Lock & Lock box. The volume of the 0.6% glutaraldehyde solution poured should be enough to immerse the top layer of bovine pericardium slices (see Figure 4 ), placed in a medical refrigerator at a storage temperature of 4°C for 7 days, and then undergo secondary processing. During the process, the folding and creasing of the bovine pericardium slices, which may damage the surface morphology of the bovine pericardium slices, should be controlled to obtain a semi-finished product; S5. Remove the bovine pericardium slices from the semi-finished product one by one from top to bottom and place them in a new Lock & Lock box. The bovine pericardium slices should be laid out and stacked in the center of the Lock & Lock box in order, and stored separately according to 20 bovine pericardium slices in a box. If there are less than 20 bovine pericardium slices, store them in a separate box according to the actual number. One person gently presses the top of the bovine pericardium slices in the Lock & Lock box that has completed the previous operation with the palm of his hand. Another person uses a 500mL graduated cylinder filled with 0.3% glutaraldehyde solution to pour 0.3% glutaraldehyde solution into the Lock & Lock box containing the transferred bovine pericardium slices. The solution should be poured slowly along the inner wall of the Lock & Lock box. The volume of the 0.3% glutaraldehyde solution should be enough to immerse the top layer of bovine pericardium slices. Finally, cover the box with a lid and store it in a medical refrigerator at a storage temperature of 4°C to obtain the finished product. The thickness of the finished valve material is 0.5mm.
[0041] Example 2: This example differs from Example 1 in that: The fixing cloth is the fixing cloth prepared in Preparation Example 5; The storage temperature during the primary and secondary treatments in S4 was 4°C; S5, the semi-finished product is first placed in a polylysine composite solution and immersed in a polylysine solution, immersed at 35 ° C for 60 min, and then the phosphatidylserine solution is added and immersed for 30 min. The polylysine solution and the phosphatidylserine solution together constitute a polylysine composite solution, and the polylysine solution and the phosphatidylserine solution are prepared using the polylysine solution and phosphatidylserine solution prepared in Preparation Example 1. The mass ratio of the polylysine solution and the phosphatidylserine solution in the polylysine composite solution is 1:0.15, and a fixed treatment is performed; then it is placed in the magnesium chloride composite solution prepared in Preparation Example 2 and immersed at 35 ° C for 30 min to complete the secondary fixation treatment. After washing 3 times with physiological saline, the semi-finished product is fixed. Remove the bovine pericardium slices one by one from top to bottom and place them in a new Lock & Lock box. The bovine pericardium slices should be laid out in order and stacked in the center of the Lock & Lock box. Store them in separate boxes of 20 bovine pericardium slices. If there are less than 20 slices, store them in separate boxes according to the actual number. One person gently presses the top of the bovine pericardium slices in the Lock & Lock box that has completed the previous operation with the palm of their hand. Another person uses a 500mL graduated cylinder filled with 0.3% glutaraldehyde solution to pour 0.3% glutaraldehyde solution into the Lock & Lock box containing the transferred bovine pericardium slices. The solution should be poured slowly along the inner wall of the Lock & Lock box. The volume of the 0.3% glutaraldehyde solution should be sufficient to immerse the top layer of bovine pericardium slices. Finally, cover the box with a lid and store it in a medical refrigerator at a storage temperature of 4°C to obtain the finished product.
[0042] Example 3: This example differs from Example 2 in that: In S2, the 0.3% glutaraldehyde solution was replaced with a 0.28% glutaraldehyde solution; In S3, the fixed cloth is gently squeezed to remove 60% of the liquid; the dry cloth is 2 layers; In S4, the 0.3% glutaraldehyde solution is replaced with a 0.28% glutaraldehyde solution; the 0.6% glutaraldehyde solution is replaced with a 0.58% glutaraldehyde solution; the storage temperature during the primary treatment and secondary treatment is 8°C; The mass ratio of the polylysine solution to the phosphatidylserine solution in S5 is 1:0.1; the calcium chloride composite solution adopts the calcium chloride composite solution prepared in Preparation Example 3.
[0043] Example 4: This example differs from Example 2 in that: In S2, the 0.3% glutaraldehyde solution was replaced with a 0.32% glutaraldehyde solution; In S3, the fixed cloth is gently squeezed to remove 70% of the liquid; the dry cloth is 4 layers; In S4, the 0.3% glutaraldehyde solution was replaced with a 0.32% glutaraldehyde solution; the 0.62% glutaraldehyde solution was replaced with a 0.58% glutaraldehyde solution; the storage temperature during the primary treatment and secondary treatment was 2°C; The mass ratio of the polylysine solution to the phosphatidylserine solution in S5 is 1:0.2; the calcium chloride composite solution adopts the calcium chloride composite solution prepared in Preparation Example 4.
[0044] Example 5: This example differs from Example 2 in that: In S5, the phosphatidylserine solution was replaced with an equal mass of polylysine solution.
[0045] Example 6: This example differs from Example 2 in that: No magnesium chloride composite solution was added for secondary fixation in S5.
[0046] Example 7: This example differs from Example 2 in that: The magnesium chloride composite liquid raw material in S5 is replaced by the polyvinyl alcohol-1799 solution with the magnesium chloride solution of equal mass.
[0047] Example 8: This example differs from Example 2 in that: The polyester fiber cloth is a common commercially available polyester fiber cloth.
[0048] Comparative Example Comparative Example 1: The difference between this preparation example and Example 1 is that: The storage temperature in S4 and S5 was changed from 4°C to 25°C.
[0049] Comparative Example 2: This preparation example differs from Example 1 in that: S2. Place the bovine pericardium slices on a polycarbonate plate, fix the four corners at four points, and then soak them in 0.3% glutaraldehyde solution for 48 hours. Then remove the bovine pericardium slices and store them in boxes of 20 slices to obtain the finished product.
[0050] Performance testing 1. Mechanical properties testing The methods of Examples 1-8 and Comparative Examples 1-2 were used to prepare biological valve materials, respectively. With reference to T / CSBM0031-2023 General Requirements for Animal-Derived Pericardial Leaflets, the elongation, tensile strength, elastic modulus, and heat shrinkage temperature were tested and the data were recorded.
[0051] 2. Anti-calcification detection The biological valve materials were prepared by the methods of Examples 1-2 and 5-7, respectively. The calcium content was detected and the data were recorded by subcutaneous implantation in rats according to YY / T1859-2022, Anti-calcification Evaluation of Animal-derived Cardiovascular Implants.
[0052] Table 1 Performance Test Table (“ / ” in the table indicates that the corresponding embodiment or comparative example was not tested for the item, so there is no data) It can be seen from Examples 1-4 and Table 1 that the biofilm material prepared in the present application has high strength, good mechanical properties and good stability, and can extend the service life of the bioprosthetic valve material.
[0053] Combining Example 2 and Examples 5-8 and Table 1, it can be seen that in Example 5S5, the phosphatidylserine solution is replaced by a polylysine solution of equal mass. Compared with Example 2, the breaking load and breaking strength of Example 5 are lower than the corresponding data of Example 2, indicating that the addition of phosphatidylserine can increase the cross-linking density of the biological valve material, thereby improving the strength, anti-calcification ability and stability of the biological valve material.
[0054] In Example 6S5, no magnesium chloride composite liquid was added for secondary fixation treatment. Compared with Example 2, the breaking load and breaking strength of Example 6 were lower than the corresponding data of Example 2, indicating that the magnesium chloride composite liquid fixed and blocked the biological valve material, further improved the strength and mechanical properties of the biological valve material, extended the service life and durability of the biological valve material, and also improved the anti-calcification ability of the biological valve material.
[0055] In Example 7S5, the magnesium chloride composite liquid raw material is replaced by the polyvinyl alcohol-1799 solution with the magnesium chloride solution of equal mass. Compared with Example 2, the breaking load and breaking strength of Example 7 are lower than the corresponding data of Example 7, indicating that polyvinyl alcohol-1799 is connected with polylysine and phosphatidylserine to form a barrier, further improving the strength and durability of the biological valve material, and also improving the anti-calcification ability of the biological valve material.
[0056] The polyester fiber cloth in Example 8 is a common commercially available polyester fiber cloth. Compared with Example 2, the breaking load and breaking strength of Example 8 are lower than the corresponding data of Example 2, indicating that the connection effect of polyethylene glycol and glutaraldehyde is utilized to further improve the cross-linking and fixing effect of the paving, thereby improving the strength and stability of the biological valve material.
[0057] Combining Example 1 and Comparative Example 1 with Table 1, it can be seen that cross-linking treatment of bovine pericardium slices at room temperature has an impact on their strength.
[0058] It can be seen from Example 1 and Comparative Example 2 and Table 1 that fixing the bovine pericardium piece with a hard steel plate affects its flexibility and strength.
[0059] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed, but as long as they are within the scope of the claims of the present application, they are protected by the patent law.
Claims
1. A method for laying out a bioprosthetic valve material, characterized in that: The steps include: S1. Fresh bovine pericardium is washed, de-fatted, and decellularized to obtain bovine pericardium slices for later use; S2. Prepare a fixing cloth soaked in a 0.28-0.32% glutaraldehyde solution and set aside; S3. Lay the bovine pericardium slice flat on the fixing cloth with the rough side facing up and the smooth side facing down. After venting, repeat the above process for the second bovine pericardium slice, alternating between the bovine pericardium slice and the fixing cloth. After venting, lay a dry cloth on the top fixing cloth to obtain the fixed bovine pericardium slice. S4. Preliminary treatment of the fixed bovine pericardium slice with a 0.28-0.32% glutaraldehyde solution, wherein the storage temperature is 2-8° C.; then, the preliminarily treated bovine pericardium slice and the fixing cloth are packaged separately, and the bovine pericardium slice is soaked in a 0.58-0.62% glutaraldehyde solution for a secondary treatment, wherein the storage temperature is 2-8° C., to obtain a semi-finished product; S5. The semi-finished product is post-processed, preserved, and finally stored at 2-8°C to obtain the finished product.
2. A bioprosthetic valve material paving method according to claim 1, characterized in that: In S2, the glutaraldehyde solution is poured into the Lock&Lock box to immerse the fixing cloth.
3. The method for laying out a bioprosthetic valve material according to claim 1, characterized in that: S3: gently squeeze the fixing cloth to remove 60-70% of the liquid, fix it in the center of the bottom of the Lock & Lock box, then squeeze out the bubbles, wipe off the surface liquid of the bovine pericardium slice, stretch it flat, and lay the bovine pericardium slice flat on the fixing cloth with the rough side facing up and the smooth side facing down. After venting, repeat the above operation for the second bovine pericardium slice, so that the bovine pericardium slices and the fixing cloth are laid alternately. After venting, lay a dry cloth on the surface of the top layer of the fixing cloth to obtain a fixed bovine pericardium slice.
4. A bioprosthetic valve material paving method according to claim 3, characterized in that: The dry cloth has 2 to 4 layers and is polyester fiber cloth.
5. A bioprosthetic valve material paving method according to claim 4, characterized in that: After the bovine pericardium sheet, the fixing cloth and the dry cloth are laid out, the total height is less than 2 / 3 of the Lock & Lock box.
6. The method for laying out a bioprosthetic valve material according to claim 1, characterized in that: The specific steps of post-processing in S5 are as follows: The semi-finished product is first fixed in a polylysine composite solution, then fixed for a second time in a magnesium chloride composite solution, washed, and then immersed in a glutaraldehyde solution.
7. A bioprosthetic valve material laying method according to claim 6, characterized in that: The polylysine composite solution is composed of a polylysine solution and a phosphatidylserine solution in a mass ratio of 1:0.1-0.
2. During the secondary cross-linking treatment, the polylysine solution is first added for treatment, and then the phosphatidylserine solution is added for treatment.
8. The method for laying out a bioprosthetic valve material according to claim 6, characterized in that: The magnesium chloride composite solution consists of a magnesium chloride solution and a polyvinyl alcohol-1799 solution in a mass ratio of 1:0.4-0.
6.
9. The method for laying out a bioprosthetic valve material according to claim 1, characterized in that: The fixing cloth is made of polyester fiber cloth.
10. A bioprosthetic valve material laying method according to claim 9, characterized in that: The polyester fiber cloth is treated as follows: the pretreated polyester fiber cloth is immersed in physiological saline, taken out and dried, then placed in a polyethylene glycol-silver powder composite liquid for immersion and dispersion treatment, and then the pretreated polyester fiber cloth is taken out and dried to obtain the polyester fiber cloth.
Citation Information
Patent Citations
Biological membrane and preparation method thereof
CN105963782A
Pretreatment method of bovine pericardial tissue for manufacturing biovalve
CN112206350A
Biological valve treatment method and biological valve dry piece
CN119971144A
Process for preparing biological material as artificial heart valve
CN1279114A
Artificial heart valve, base material for regenerative medicine, and its method
JP2006158494A